EVALUASI DAMPAK KEBIJAKAN PELATIHAN PEMASARAN DIGITAL BAGI PELAKU USAHA MIKRO KECIL, DAN MENENGAH (UMKM) DAERAH KOTA TANJUNGPINANG - Erva Afriyana; Dian Prima Safitri; Okky Rizki Azizi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study evaluates the impact of digital marketing training policies on Micro, Small, and Medium Enterprises (MSMEs) in Tanjungpinang City. Its primary objective is to analyze the extent to which these training programs enhance digital capacity, encourage the adoption of online marketplaces, and contribute to improved business performance among MSMEs. This study employs a qualitative approach, with data collected through observation, in-depth interviews, and documentation. Data analysis was conducted using NVivo software, encompassing data reduction, data presentation, and drawing conclusions. The results indicate that digital marketing training has had a significant positive impact. Participants saw an increase in their digital knowledge and skills, such as the use of social media, graphic design applications, and online marketplaces for promotion and sales. A shift in behavior occurred, as MSMEs began actively utilizing digital platforms and implementing digital marketing strategies in a more structured manner. The identified economic impacts include expanded market reach, an increase in the number of customers, and higher sales revenue. However, the program’s effectiveness has not been uniformly optimal due to constraints such as limited training duration, a lack of post-training mentoring, and the continued uneven distribution of information. Recommendations include the need to expand the program’s reach, increase the intensity of training, and strengthen the system of ongoing mentoring to maximize the positive impact on MSMEs in Tanjungpinang City.